Pekerja Muda dan Ancaman Deskilling-Skill Trap di Sektor Transportasi Berbasis Daring - Dian Fatmawati; Falikul Isbah; Amelinda Pandu Kusumaningtyas (Universitas Gadjah Mada, 2019)
Many internet technological discoveries have shaped many aspects of human life, including economic transaction for goods and services. Online-based transportation service is one form of digital economies, which was born out of the current progress of internet applications integrated to smartphones. Motorcycle ride-sharing has been existing in Indonesia from a long time ago, but it becomes much more popular after being offered through internet apps on smartphones. This Article base on mixed-methods research by using survey and in-depth interview as collecting data technically. Based on research on the workers of Go-Jek online-based transportation service in three cities (Jakarta, Yogyakarta, and Banyuwangi), founded that this job has absorbed a very large number of workers, and the majority of them are young workers. The new things in this job are its job design is fully based on the usage of the algorithm, namely in communicating, supervising, rewarding, and punishing the workers. This affects the job process which provides an ultimate authority to the company to make any decision over the workers. Lastly, we especially analysis the process of deskilling and skill trap in which the young workers do not have an opportunity to get the rank promotion, career mobility, and income up-grading. Considering they are still young and have a very long productive age, this issue is urgent to study further by policymakers in the employment sector.